Repeater F‐waves are signs of motor unit pathology in polio survivors - Hachisuka, Akiko (Muscle Nerve, 2015)
INTRODUCTION: The purpose of this study was to determine whether F‐waves reveal electrophysiological features of anterior horn cells in polio survivors. METHODS: Forty‐three polio survivors and 20 healthy controls underwent motor nerve conduction studies of the median and tibial nerves bilaterally, including sampling of F‐waves elicited by 100 stimuli and the determination of motor unit number estimation (MUNE). RESULTS: A significant increase in abnormally stereotyped (“repeater”) F–waves and a reduction of F‐wave persistence were observed in both nerves in the polio group as compared with the control group. Repeater F‐waves had a negative correlation with MUNE. CONCLUSIONS: These trends in F‐wave persistence and repeater F‐waves after motor unit loss are characteristic findings in polio survivors. Repeater F‐waves are a sign of motor unit pathology. Muscle Nerve 51:680–685, 2015